2014
DOI: 10.1186/1472-6882-14-507
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive potential of the aqueous extract which combine leaf of Persea americana Mill. (Lauraceae), stems and leaf of Cymbopogon citratus (D.C) Stapf. (Poaceae), fruits of Citrus medical L. (Rutaceae) as well as honey in ethanol and sucrose experimental model

Abstract: BackgroundThe present study was designed to evaluate the effects of the aqueous extract obtained from the mixture of fresh leaf of Persea americana, stems and fresh leaf of Cymbopogon citratus, fruits of Citrus medica and honey on ethanol and sucrose induced hypertension in rats.MethodsRats were divided into eight groups of 6 rats each and daily treated for 5 weeks. The control group received distilled water (1 mL/kg) while rats of groups 2, 3 and 4 received ethanol 40 degrees (3 g/kg/day), 10% sucrose as drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 39 publications
(47 reference statements)
5
35
0
3
Order By: Relevance
“…It is also known as ‘alligator pear’ or ‘butter pear’ (Lacerda et al , ). Avocado is consumed, not only for its flavor, but also for its high nutritional value and beneficial health effects (Meyer and Terry, ) including hypoglycaemic (Ezejiofor et al , ), antihypertensive (Dzeufiet et al , ), antioxidant (Nagaraj et al , ), anti‐obesity (Monika and Geetha, ), hypolipidemic (Pahua‐Ramos et al , ) (Fig. ), antilithiasis (Wientarsih et al , ), anticonvulsant (Ojewole and Amabeoku, ), antimicrobial (Pradeep et al , ), antiprotozoal and antimycobacterial (Jiménez‐Arellanes et al , ), hepatoprotective (Mahmoed and Rezq, ), antiosteoarthritis (Christiansen et al , ) and chemo‐protective (Paul et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…It is also known as ‘alligator pear’ or ‘butter pear’ (Lacerda et al , ). Avocado is consumed, not only for its flavor, but also for its high nutritional value and beneficial health effects (Meyer and Terry, ) including hypoglycaemic (Ezejiofor et al , ), antihypertensive (Dzeufiet et al , ), antioxidant (Nagaraj et al , ), anti‐obesity (Monika and Geetha, ), hypolipidemic (Pahua‐Ramos et al , ) (Fig. ), antilithiasis (Wientarsih et al , ), anticonvulsant (Ojewole and Amabeoku, ), antimicrobial (Pradeep et al , ), antiprotozoal and antimycobacterial (Jiménez‐Arellanes et al , ), hepatoprotective (Mahmoed and Rezq, ), antiosteoarthritis (Christiansen et al , ) and chemo‐protective (Paul et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Several bioassays have shown pharmacological evidence of some Cymbopogon species. C. citratus was found to express pharmacologic effects as cytotoxicity (Kpoviessi et al 2014), insecticidal (Pinto et al 2013), antitrypanosomal (Kpoviessi et al 2014), anti-diabetic (Bharti et al 2013), antihypertensive (Dzeufiet et al 2014), antioxidant (Somparn et al 2014), anti-inflammatory (Tavares et al 2015), hepatoprotective (Rahim et al 2014), antifungal (Amornvit et al 2014), and antimalaria (Chukwuocha et al 2016). Biological assay of C. martinii extracts revealed a potential of this species as a strong antioxidant (Andrade et al 2014a), and anti-inflammatory (Andrade et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that calcium disarrangement and free radical formation play a role in hepatotoxicity and nifedipine was shown to decrease MDA, increase GSH and SOD in diethyl dithiocarbamate-induced hepatic toxicity in rats [16]. Additionally, Nifedipine was shown to increase the activity of superoxide dismutase and catalase; elevate the contents of GSH and nitrites; and decrease the MDA levels [17].…”
Section: Discussionmentioning
confidence: 99%